2013
DOI: 10.1038/ncomms2505
|View full text |Cite
|
Sign up to set email alerts
|

One mechanism contributing to co-variability of the Atlantic inflow branches to the Arctic

Abstract: The two-branched inflow of warm and saline Atlantic Water to the Arctic is the major contributor of oceanic heat to the Arctic climate system. However, while the Atlantic Water entering the Arctic through the Fram Strait retains a large part of its heat as it flows along the Arctic continental slope, the branch flowing through the shallow Barents Sea releases a substantial amount of heat to the atmosphere. Hence, the pathway of the Atlantic Water into the Arctic to a large degree determines the short term fate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
82
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 28 publications
(28 reference statements)
17
82
0
Order By: Relevance
“…For example, analysis of long-term mooring records demonstrated that 2008-10 changes in the thermohaline state of the eastern Eurasian basin led to a reverse (i.e., shallow to left) direction of the along-slope currents, thus altering the general perception on the commonly accepted cyclonic regime of AW circulation in the central Laptev Sea (Pnyushkov et al 2015). In support of this finding, Lien et al (2013) showed that wind forcing near the Barents Sea shelf break may partition the relative strengths of the Fram Strait and Barents branches of the boundary current.…”
Section: Heat Transport In the Arctic Ocean: Description And Mechanismssupporting
confidence: 60%
See 1 more Smart Citation
“…For example, analysis of long-term mooring records demonstrated that 2008-10 changes in the thermohaline state of the eastern Eurasian basin led to a reverse (i.e., shallow to left) direction of the along-slope currents, thus altering the general perception on the commonly accepted cyclonic regime of AW circulation in the central Laptev Sea (Pnyushkov et al 2015). In support of this finding, Lien et al (2013) showed that wind forcing near the Barents Sea shelf break may partition the relative strengths of the Fram Strait and Barents branches of the boundary current.…”
Section: Heat Transport In the Arctic Ocean: Description And Mechanismssupporting
confidence: 60%
“…This heat transported into the Arctic Ocean is supplied to the deep-ocean interior, yielding a basin average of 5 W m -2 heat f lux (Pnyushkov et al 2015). In contrast, the Barents Sea branch delivers little heat to the deep Arctic basins, as it cools and freshens rapidly in the western Barents Sea prior to subducting along the Polar Front (Lien and Trofimov 2013). Enhanced inf low of warm AW was observed in the 2000s, resulting in exceptionally warm AW layer temperatures with no precedent since at least the 1950s (Polyakov et al 2012b) and likely over the past 2000 years (Spielhagen et al 2011).…”
Section: Heat Transport In the Arctic Ocean: Description And Mechanismsmentioning
confidence: 99%
“…Here, we provide a mechanistic understanding of the response of sea ice to ocean heat anomalies modulated by changes in volume transport. Continental shelf waves induced by atmospheric-driven Ekman transports and the piling up of water toward the coast of Norway (Gill and Schumann 1974;Ingvaldsen et al 2004;Skagseth et al 2011;Lien et al 2013a) are shown to result in a coherent ocean heat transport anomaly through the Barents Sea that impacts the sea ice cover concomitantly. We combine observations and a numerical ocean general circulation model to study in detail a period of increased Atlantic water flow through the Barents Sea in February 1993 and quantify the relationship between this increased oceanic heat transport and a simultaneous reduction in the sea ice cover.…”
mentioning
confidence: 99%
“…Thus, the area prone to a CO 2 fertilization response will probably be restricted to the MIZ, which will migrate polewards, following the ice edge, to occupy a diminishing fraction of the Arctic Ocean with climate warming and be replaced by an annually ice-free ocean 26,27 . Furthermore, CO 2 limitation is unlikely to affect the southern sector of the European Arctic owing to the invasion of the Arctic by increasingly warmer and CO 2 -rich Atlantic waters through the two-branched inflow of Atlantic Water along the Barents Sea and the Fram Strait 28 .…”
mentioning
confidence: 99%